Fiqh muamalat case study: cryptocurrency in perspective Islam / Nur Halimatus Sa'diyah Kamarudun … [et al.] - Kamarudun, Nur Halimatus Sa'diyah; Ibrahim, Nihayah; Mahadir, Siti Ainin Sofia; Mohd Masri, Siti Nur Nadhira Athira (2023)
Cryptocurrency refers to a type of digital asset that uses distributed ledger, or blockchain, technology to enable a secure transaction. Although the technology is widely misunderstood, many central banks are considering launching their own national cryptocurrency. Detailed information on the history of every transaction in the bitcoin industry is publicly available, in contrast to the majority of data in financial economics. Additionally, empirically oriented research is only now getting started, providing academia with a remarkable opportunity for research. A kind of payment known as cryptocurrency can be used to buy and sell items and services online. Numerous businesses have created their own currencies, frequently referred to as tokens, which can be exchanged for the specific product or service that the business offers. Imagine them as we would casino chips or arcade tokens. To access the good or service, we must exchange actual money for the cryptocurrency. Blockchain technology is how cryptocurrencies function. Blockchain is a decentralised system that tracks and manages transactions across numerous computers. Part of the appeal of this technology is its security.